Blenderized tube feeding for children: an integrative review - Érica Patrícia Cunha Rosa Schmitz; Eliziane Costa da Silva; Ozeas de Lima Lins Filho; Margarida Maria de Castro Antunes; Kátia Galeão Brandt (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To analyze scientific evidence on the use of blenderized tube feeding in children regarding nutritional composition, family satisfaction, and health outcomes. Data source: Survey was conducted in the PubMed, Scopus, Embase, and Virtual Health Library (VHL) databases using the following search terms: blenderized tube feeding OR blended tube feeding OR homemade OR pureed AND enteral nutrition AND enteral tube. The methodological quality of the selected articles was evaluated using the Critical Appraisal Skill Programme and Hierarchical Classification of Evidence. Data synthesis: After analysis, 11 articles were included in the present review. Most studies demonstrated improvements in health outcomes and greater family satisfaction after replacing the commercial enteral feeding with blenderized tube feeding. Conclusions: When guided and monitored by the healthcare team, a blenderized tube feeding ensures an adequate nutritional composition. The use of this method is also associated with positive health outcomes such as reductions in gastrointestinal symptoms and hospitalizations. Moreover, a high frequency of family satisfaction was verified.%